Metabolic engineering of oleaginous fungus Mortierella alpina for high production of oleic and linoleic acids. (December 2017) - Sakamoto, Takaiku; Sakuradani, Eiji; Okuda, Tomoyo; Kikukawa, Hiroshi; Ando, Akinori; Kishino, Shigenobu; Izumi, Yoshihiro; Bamba, Takeshi; Shima, Jun; Ogawa, Jun
Highlights: LA or OA high-producing strains were obtained by molecular breeding of M. alpina . The production of LA and OA reached 3.32 and 3.85 g/L, respectively, on the 5th day. The Δ6II RNA level in the transformant was 8 times as high as the wild strain. Abstract: The aim of this work was to study the molecular breeding of oleaginous filamentous Mortierella alpina for high production of linoleic (LA) or oleic acid (OA). Heterologous expression of the Δ12-desaturase (DS) gene derived from Coprinopsis cinerea in the Δ6DS activity-defective mutant of M. alpina increased the LA production rate as to total fatty acid to 5 times that in the wild strain. By suppressing the endogenous Δ6I gene expression by RNAi in the Δ12DS activity-defective mutant of M. alpina, the OA accumulation rate as to total fatty acid reached 68.0%. The production of LA and OA in these transformants reached 1.44 and 2.76 g/L, respectively, on the 5th day. The Δ6I transcriptional levels of the RNAi-treated strains were suppressed to 1/10th that in the parent strain. The amount of Δ6II RNA in the Δ6I RNAi-treated strain increased to 8 times that in the wild strain.